ETHNOLOGY ROUTES OF REPRESENTATIVES EDUCATIONAL INSTITUTIONS GALICIA ON THE TERRITORY OF RURAL SETTLEMENTS IN THE ХІХ CENTURY - Дудка, Т. Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The questions of content fullness research travels, outlined the geography of their distribution with regard to spatial-temporal determinants, described the contribution of representatives of educational institutions of Galicia in the development of ethnology and folklore – ethnographic research area